2016
DOI: 10.3168/jds.2015-10745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quebracho-chestnut tannin extracts at 2 dietary crude protein levels on performance, rumen fermentation, and nitrogen partitioning in dairy cows

Abstract: Our objective was to determine the effects of a tannin mixture extract on lactating cow performance, rumen fermentation, and N partitioning, and whether responses were affected by dietary crude protein (CP). The experiment was conducted as a split-plot with 24 Holstein cows (mean ± standard deviation; 669±55kg of body weight; 87±36 d in milk; 8 ruminally cannulated) randomly assigned to a diet of [dry matter (DM) basis] 15.3 or 16.6% CP (whole plot) and 0, 0.45, 0.90, or 1.80% of a tannin mixture in three 4×4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
96
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(131 citation statements)
references
References 33 publications
(60 reference statements)
30
96
4
1
Order By: Relevance
“…However, the effective reduction of CP degradation was not proportional to the two-fold increase in CT (Bruno- Soares et al, 2011). Quebracho tannin extract (QTE) is a commercially available CT source from Schinopsis spp., consistently reported to decrease ruminal CP degradation at multiple dietary fiber (Dschaak et al, 2011) and CP levels (Aguerre et al, 2016). Responses appear to be doserelated as increasing inclusion from 1 to 6% of DM linearly decrease ruminal CP degradation (Ahnert et al, 2015).…”
Section: Interactions Between Condensed Tannins and Protein In The Dietmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the effective reduction of CP degradation was not proportional to the two-fold increase in CT (Bruno- Soares et al, 2011). Quebracho tannin extract (QTE) is a commercially available CT source from Schinopsis spp., consistently reported to decrease ruminal CP degradation at multiple dietary fiber (Dschaak et al, 2011) and CP levels (Aguerre et al, 2016). Responses appear to be doserelated as increasing inclusion from 1 to 6% of DM linearly decrease ruminal CP degradation (Ahnert et al, 2015).…”
Section: Interactions Between Condensed Tannins and Protein In The Dietmentioning
confidence: 90%
“…However, microbial protein production was improved in a birdsfoot trefoil diet suggesting a more efficient use of dietary N when a CT-containing forage was offered in replacement for alfalfa. As rumen NH 3 is reduced, CT shift N excretion from the urine to feces (Deaville et al, 2010;Williams et al, 2011;Hymes-Fecht et al, 2013;Ahnert et al, 2015;Orlandi et al, 2015;Aguerre et al, 2016), which may substantially improve environmental sustainability of ruminant production through reduced nitrous oxide emissions from manure (Powell et al, 2010). The effect of CT on microbial protein synthesis and microbial growth efficiency are much less clear compared with the well-established responses on ruminal CP degradation and NH 3 concentrations.…”
Section: Interactions Between Condensed Tannins and Protein In The Dietmentioning
confidence: 99%
“…The effects of plant extracts rich in polyphenolic compound on total VFA and VFA profiles varied among studies, and are dependent on source, rate and dosage of polyphenolic compound. On the other hand, Carulla et al (2005) found no effect of tannins on total VFA in sheep supplemented with black wattle tree, whereas, Beauchemin et al (2007) reported a decrease in acetate molar proportion when cattle were fed quebracho, with a tendency to a decrease in total VFA. In the present study, PPE decreased the concentration of BCVFA and increased the concentration of acetate.…”
Section: Effects Of Pomegranate Extractmentioning
confidence: 93%
“…Aguerre et al (2010) reported that at a lower concentration of condensed tannins (4.5 g tannins extracts kg…”
Section: Effect Of Sainfoin Hay Extractmentioning
confidence: 99%
See 1 more Smart Citation